PEMBERDAYAAN PENGRAJIN BAMBU DI KELURAHAN KINILOW KECAMATAN TOMOHON UTARA KOTA TOMOHON - Afny Rompas; Jenny Baroleh; Noortje Marsellanie Benu (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine the empowerment of bamboo craftsmen in Kinilow Village. The research was conducted from October to December 2019. The data used are primary and secondary data. Primary data were obtained through interview surveys using questionnaires and documentation. Secondary data were obtained from literature studies and related agencies, namely the Tomohon Industry and Trade Office and the Kinilow Urban Village government. The sampling method was purposive (purposive sampling) on 7 respondents of bamboo craftsmen in Kinilow Village. The data analysis used in this research is descriptive qualitative analysis and the data obtained are presented in tabular form. The results showed that the process of empowering bamboo craftsmen in Kinilow Village occurred through the implementation of empowerment which included the awareness and behavior formation stage, the knowledge transformation stage, and the intellectual ability improvement stage. The implementation of empowerment is carried out through entrepreneurship training which includes two objectives, namely providing counseling to improve product quality and providing training in product development skills and marketing strategies. As well as assistance provided by the Dinas.